A proximate remove: queering intimacy and loss in The tale of Genji - Jackson, Reginald R. (New interventions in japanese studies, 2021)
Preface : benefits of the doubt : questioning discipline and the risks of queer reading -- Introduction -- Translation fantasies and false flags : desiring and misreading queerness in premodern Japan -- Chivalry in shambles : fabricating manhood amidst architectural disrepair -- Going through the motions : half-hearted courtship and the topology of queer shame -- Queer affections in exile : textual mediation and exposure at Suma Shore -- From harsh stare to reverberant caress : queer timbres of mourning in "The Flute" -- Conclusion : learning from loss -- Afterword : teaching removal.